Gaya Komunikasi Konten Kreator TikTok dalam Membangun Engagement Followers: Tinjauan Literatur pada Era Digital Public Relations - Feza Akdayori Putra; Rahim, Umar Abdur; Kemala, Intan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
The rapid growth of TikTok has transformed digital communication practices and created new opportunities for content creators to establish stronger relationships with their audiences. From the perspective of Digital Public Relations, communication style plays a crucial role in influencing follower engagement and enhancing the effectiveness of online interactions. This study aims to examine the communication styles employed by TikTok content creators to build and strengthen follower engagement. The research adopts a qualitative approach using the Systematic Literature Review (SLR) method by analyzing relevant scholarly articles published between 2021 and 2026. The findings reveal that communication styles emphasizing authenticity, interactivity, storytelling, content consistency, and emotional connection significantly contribute to higher audience engagement, as reflected in the number of likes, comments, shares, and active participation. Furthermore, the effective use of trending content, TikTok's algorithmic features, and adaptive communication strategies strengthens relationships between content creators and followers while enhancing credibility and digital presence. The review also identifies opportunities for future research on the influence of audience characteristics, digital culture, and evolving social media algorithms on the development of sustainable engagement in digital communication.